2009
DOI: 10.1289/ehp.11497
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Childhood Respiratory Allergies in the United States

Abstract: BackgroundChildhood respiratory allergies, which contribute to missed school days and other activity limitations, have increased in recent years, possibly due to environmental factors.ObjectiveIn this study we examined whether air pollutants are associated with childhood respiratory allergies in the United States.MethodsFor the approximately 70,000 children from the 1999–2005 National Health Interview Survey eligible for this study, we assigned between 40,000 and 60,000 ambient pollution monitoring data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 59 publications
(82 reference statements)
0
38
0
1
Order By: Relevance
“…The effect of the air pollution was detected in terms of emergency services and admittances in large and small cities in Brazil. Parker et al [172], in a research conducted with North-American children, came to the same conclusion: the results provide evidence of adverse health effects for children living in areas with chronic exposure to higher levels of O 3 and PM 2.5 compared with children with lower exposures.…”
Section: Social -Sanitation and Socio-environmental Factorsmentioning
confidence: 74%
“…The effect of the air pollution was detected in terms of emergency services and admittances in large and small cities in Brazil. Parker et al [172], in a research conducted with North-American children, came to the same conclusion: the results provide evidence of adverse health effects for children living in areas with chronic exposure to higher levels of O 3 and PM 2.5 compared with children with lower exposures.…”
Section: Social -Sanitation and Socio-environmental Factorsmentioning
confidence: 74%
“…This is in line with the strong consistent association observed between the distance to the nearest main road and allergic disease outcomes. Children living closer than 50 meters to a busy street had a higher probability of getting allergic symptoms, compared to children living further away (Parker, Akinbami et al, 2009). In fact, one recent Los Angeles study found that eight percent of childhood asthma cases could be associated to living close (within 250 feet) to major roadways.…”
Section: Public Health Effectsmentioning
confidence: 99%
“…The proportion of PM2.5 in the distal pulmonary tissues was found to be three times larger than that of PM10 . Around 81 million Americans live in areas that fail to meet national air quality standards for particulate matter (Parker, Akinbami et al, 2009;Gardiner, 2011). Multiple studies have reported specifically on the relation between PM-exposure and adverse health outcomes.…”
Section: Health Effects Of Exposure To Specific Air Pollutantsmentioning
confidence: 99%
See 2 more Smart Citations